Prevalence of Human Papillomavirus Infection and Cervical Cancer Screening among Riverside Women of the Brazilian Amazon - Daniel Valim Duarte; Rodrigo Covre Vieira; Elza Baía de Brito; Maria da Conceição Nascimento Pinheiro; Jeniffer do Socorro Valente Monteiro; Mário Diego Rocha Valente; Edna Aoba Yassui Ishikawa; Hellen Thais Fuzii; Maísa Silva de Sousa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose The aim of this study was to evaluate the overall and type-specific prevalence of human papillomavirus (HPV) infection among females living in riverside communities in the state of Pará, in the Eastern Brazilian Amazon. These communities are inhabited by low-income people, and are accessible only by small boats. Cervical cytology and risk factors for HPV infection were also assessed. Methods Cervical samples from 353 women of selected communities were collected both for Papanicolau (Pap) test and HPV detection. Conventional polymerase chain reaction (PCR) and real-time PCR were used to assess the overall and type-specific prevalence of HPV-16 and HPV-18, the main oncogenic types worldwide. Epidemiological questionnaires were used for the assessment of the risk factors for HPV infection. Results The mean age of the participants was 37 years (standard deviation [SD] ± 13.7). Most were married or with a fixed sexual partner (79%), and had a low educational level (80%) and family monthly income (< U$ 250; 53%). Overall, HPV prevalence was 16.4% (n = 58), with 8 cases of HPV-16 (2.3%) and 5 of HPV-18 (1.4%). Almost 70% of the women surveyed had never undergone the Pap test. Abnormal cytology results were found in 27.5% (n = 97) of the samples, with higher rates of HPV infection according to the severity of the lesions (p = 0.026). Conclusions The infections by HPV-16 and HPV-18 were not predominant in our study, despite the high prevalence of overall HPV infection. Nevertheless, the oncogenic potential of these types and the low coverage of the Pap test among women from riverside communities demonstrate a potential risk for the development of cervical lesions and their progression to cervical cancer, since the access to these communities is difficult and, in most cases, these women do not have access to primary care and public health services.